Asset ownership among women in the semi-arid tropics of India: Micro-level insights towards empowerment of women - Ravula, Padmaja; Kumar Vermula, Anil; Kasala, Kavitha; Duche, Vishwambhar; Guvvala, Anupama (International Crops Research Institute for the Semi-Arid Tropics, 2023)
Ownership of assets is an important dimension and measure of women’ agency in the rural agri-food systems. Ownership of productive assets by rural women such as agricultural land, dwellings, and livestock can translate to women’s empowerment. This paper attempts to provide deeper insights into asset ownership by rural women in the semi-arid tropics of United Andhra Pradesh and Maharashtra states of India and how it translates into empowerment/ disempowerment of these women. Data was collected from more than 1,000 women through a quantitative survey. Applied logistic regression analysis to test women’s empowerment for the three productive assets—dwelling, agricultural land, and livestock was performed. The odds ratio revealed significant results across agro-ecologies, caste group, and age. Women belonging to the drought-prone areas had greater ownership of assets and thereby showed greater input into decision-making compared to women from the assured-rainfall region and canal-irrigated region. In all three agro-ecologies, women from the backward social group were empowered compared to the forward and the scheduled-caste and scheduled-tribes groups. Implementation of women-empowerment programs in drought-prone areas emerged as one of the major drivers in enhancing women’s agency. Restrictive gender and social norms for women from forward caste limit their agency. This paper emphasizes the need for greater program and policy implementation focused on enhancing gender equality in asset ownership. By addressing the existing disparities and empowering women to access and control assets, we can foster inclusive economic growth and social progress.